The dialogue in lyrical poetry: "Teresa" and "La voz a ti debida" - Maestro, Jesús G. (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
The present article aims to offer a scientific reflection on the possibilities of realization in lyric discourse of the semiotic pracesses of creation and transformation of meaning sense: expression, signification, communication, interaction, interpretation and transduction. We will use for our analysis poetic works by two especially representative authors: Miguel de Unamuno's Teresa (1924), and Pedro Salinas' La voz a ti debida (1933). From the pragmatics of literary communication's point of view, we intend to establish a set of comparative models (or models of comparison) between both works, in order to account for the di verse analogies present in the processes of lyric enunciation, inherent emission and reception, generated in each of the poems. Finally, we aim towards a model of analysis of Iyric enunciation of general validity, thus applicable to every poem.
Keywords: Miguel de Unamuno; Pedro Salinas